PENYULUHAN SISTEM AGRIBISNIS SUATU PENDEKATAN HOLISTIK - SUPARTA, NYOMAN (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 3, No. 2 Juli 2003)
The rising issues nowadays related to the existence of chicken broiler business and agribusiness system are low added value obtained for farmers, disharmonic relationship among agribusiness system agents, and low competitive ability. On the other hand, the business and agribusiness system improvement need dynamic, creative and innovative human recourses with strong business instinct, and the ability in understanding the ethics of agribusiness system relationship well for achieving better business results. The reason of this gap might be caused by the fact that the farmers or other agribusiness sub-system agents do not fully understand the business and agribusiness system. The research has been carrying out to obtain depiction of agribusiness behavior with industrial culture, and its extension approach. The result of the research shows that application of the holistic extension of agribusiness was needed. The extension‘s objective exactly to the change of agribusiness behavior with industrial culture. The extension materials include all of production technical aspect, agribusiness management aspect, and agribusiness system relationship management aspect with industrial’s perception, so the agribusiness system businessmen’s could have the same perception and attitude about: vision, missions, business ethics, objective, goal and cooperative plan witch formulated with open way. The extension methods must be more varieties. The extension agribusiness system needs professionalism extensionists too, but usually base on the basic philosophy and principles of the extension.
Keywords: Agribusiness Behavior,Eextension of Agribusiness System, Holistic